Metabolic parameters in acne vulgaris: a case control study investigating fasting blood glucose and insulin levels in acne vulgaris - Palaniswami, Saranya; Prakash, Bhanu; Saminathan, Praveen Vasanthi (International Journal of Research in Dermatology, 2024)
Background: Influence of diet and lifestyle on acne among Indian population. Objectives were to identify the clinico-epidemiological profile of patients with Acne vulgaris and to assess the fasting plasma glucose and serum insulin levels in Acne vulgaris patients and the controls and correlate them. Methods: This was a hospital-based case-control study conducted in the Department of Dermatology, Vydehi Institute of Medical Sciences and Research Centre, Bangalore. Study included 60 cases of acne and 60 controls (age and sex matched), attending the outpatient department. After complete history, general physical, systemic and cutaneous examination, all cases were subjected to following investigation: fasting blood sugar and serum insulin levels. Results: Acne was common in the age group 18-24 yrs (70%). In almost half the patients the age of onset was between 12-18 yrs. Commonly observed site for acne was cheeks (83.3%), forehead (66.7%), nose (55%) and chin (41.7%). The risk of developing acne was 3.5 times more among smokers than non-smokers. The mean fasting blood sugar values of cases and controls when compared showed a statistically significant difference (p<0.05). Our study did not find any statistically significant difference in fasting insulin levels between cases and controls. Conclusions: There was only significant difference in the Mean fasting blood glucose in cases as compared to controls. Mean fasting serum insulin level though found to be raised in cases compared to controls, does not prove statistical significance. Fasting plasma glucose was significantly raised in grade III acne as compared to other grades.